Treatment outcome after neonatal cleft lip repair in 5-year-old children with unilateral cleft lip and palate - Košková, Olga; Vokurková, Jitka; Vokurka, Jan; Bryšova, Alena; Šenovský, Pavel; Čefelínová, Julie; Lukášová, Darina; Dorociaková, Petra; Abelovský, Juraj (International journal of pediatric otorhinolaryngology, 2016)
INTRODUCTION: The aim of this study was to assess speech outcomes and dental arch relationship of 5-year-old Czech patients with unilateral cleft lip and palate (UCLP) who have undergone neonatal cleft lip repair and one-stage palatal closure. METHODS AND MATERIALS: Twenty-three patients with UCLP, born between 2009 and 2010, were included in the study. Three universal speech parameters (hypernasality, articulation and speech intelligibility) have been devised for speech recordings evaluation. Outcomes of dental arch relationship were evaluated by applying the GOSLON Yardstick and subsequently compared with the GOSLON outcome of other cleft centers. RESULTS: Moderate hypernasality was present in most cases, the mean value for articulation and speech intelligibility was 2.07 and 1.93, respectively. The Kappa values for inter-examiner agreement for all the three speech outcomes ranged from 0.786 to 0.808. Sixty-three percent of patients were scored GOSLON 1 and 2, 26% GOSLON 3, and 10% GOSLON 4. GOSLON mean score was 2.35. Interrater agreement was very good, represented by kappa value of 0.867. CONCLUSION: The treatment protocol, involving neonatal cleft lip repair and one-stage palatal repair performed up to the first year of UCLP patient's life, has shown good speech outcomes and produced very good treatment results in regard to maxillary growth, comparable with other cleft centers.
Keywords: Age Factors; Cleft Palate; mužské pohlaví; Male; Clinical Protocols; Czech Republic; výsledek terapie; řeč; Female; Humans; Cleft Lip; lidé; maxila; ženské pohlaví; kvalita hlasu; Česká republika; Speech; Child; dítě; Dental Arch; rozštěp rtu; klinické protokoly; Treatment Outcome; Maxilla; Child, Preschool; rozštěp patra; Voice Quality; předškolní dítě; věkové faktory; zubní oblouk